RAPOC: The Rosseland and Planck opacity converter: A user-friendly and fast opacity program for Python - Mugnai, Lorenzo V.; Modirrousta-Galian, Darius (Experimental astronomy, 2023)
RAPOC (Rosseland and Planck Opacity Converter) is a Python 3 code that calculates Rosseland and Planck mean opacities (RPMs) from wavelength-dependent opacities for a given temperature, pressure, and wavelength range. In addition to being user-friendly and rapid, RAPOC can interpolate between discrete data points, making it flexible and widely applicable to the astrophysical and Earth-sciences fields, as well as in engineering. RAPOC uses ExoMol , DACE , or any user defined input data, provided that it is in a readable format. In this paper, we present the RAPOC code and compare its calculated Rosseland and Planck mean opacities with other values in the literature. RAPOC is open-source and available on Pypi and GitHub.